Power for sport performance - Bishop, Tim; Shiner, Jay; Fink, Doug (Illnois : Human Kinetic, 2007)
Power your way to dominance on the field, court, or mat. Power for Sports Performance provdies tools to build a program for your needs, your sport, and your goals
Introduction -- Assessment -- Power-base building -- Complex power training -- Power progression -- Power plus -- Conclusion
Title from title screen
Camera, Dave Strong, John Eisenhour ; editor, Chris Clark
Keywords: Physical education and training; Athletes -- Training of; Physical fitness